Secondary battery and manufacturing method thereof

KR103020956B1Active Publication Date: 2026-09-16LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020220034514
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-03-21
Publication Date
2026-09-16
Estimated Expiration
2042-03-21

Smart Images

  • Figure 112022029961690-PAT00001
    Figure 112022029961690-PAT00001
  • Figure 112022029961690-PAT00002
    Figure 112022029961690-PAT00002
  • Figure 112022029961690-PAT00003
    Figure 112022029961690-PAT00003
Patent Text Reader

Abstract

The present invention relates to a lithium secondary battery and a method for manufacturing the same. The lithium secondary battery has the advantage of excellent safety by preventing leakage of the liquid electrolyte while achieving high ion conductivity, by introducing a coating layer containing an azo-based thermal initiator on the inner surface of a battery case into which an electrode assembly is inserted, and by including a polymer having reactive acrylic groups in the liquid electrolyte to induce a cross-linking reaction between them, a gel polymer can be selectively included at a high density on the outer surface of the electrode assembly, specifically in the space between the electrode assembly and the battery case.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a lithium secondary battery and a method for manufacturing the same. Background Technology

[0003] With the rapid development of the electrical, electronic, telecommunications, and computer industries in recent years, the demand for high-performance and high-stability rechargeable batteries is gradually increasing. In particular, driven by the trend toward miniaturization and lightweighting of these electronic and telecommunications devices, there is a demand for thin-film and miniaturization of lithium-ion batteries, which are key components in this field.

[0004] Lithium secondary batteries can be divided into lithium-ion batteries using liquid electrolytes and lithium-polymer batteries using polymer electrolytes, depending on the electrolyte applied.

[0005] Lithium-ion batteries have the advantage of high capacity, but because they use a liquid electrolyte containing lithium salts, there is a risk of leakage and explosion, and countermeasures for this result in a complex battery design.

[0006] On the other hand, lithium polymer batteries differ from lithium-ion batteries in that the separator between the positive and negative electrodes is made of a polymer, and said polymer separator can also function as an electrolyte.

[0007] The electrolyte of a lithium polymer battery can be used as a solid polymer electrolyte or a gel polymer electrolyte containing a liquid electrolyte, which exhibits high safety and flexibility, allowing it to be developed into various forms such as small or thin films.

[0008] However, since gel polymer electrolytes exhibit low ionic conductivity at room temperature, the performance of the battery is not high compared to liquid electrolytes, and there is a limitation in that the safety of the battery is not sufficiently realized depending on the reaction rate of the gel polymer electrolyte. Specifically, if the reaction rate of the organic component contained in the gel polymer electrolyte is slow—in other words, if the reaction time of the gel polymer electrolyte is long—not only is processability low, but there is also a problem of reducing the safety of the battery by inducing low reactivity of the gel polymer electrolyte. On the other hand, if the reaction rate of the organic component is fast, the storage stability of the gel polymer electrolyte is poor, and there is a limitation in that the reaction uniformity of the reacted gel electrolyte is low or it is difficult to form a uniform adhesion surface with the electrode or separator, resulting in reduced adhesion.

[0009] Therefore, there is a need to develop secondary batteries with excellent charge / discharge performance and lifespan, which have low risk due to electrolyte leakage and other factors, as well as superior electrical properties such as ion conductivity. The problem to be solved

[0011] Accordingly, the objective of the present invention is to provide a lithium secondary battery with improved safety by preventing leakage of the liquid electrolyte while achieving high ionic conductivity by including a liquid electrolyte, and a method for manufacturing the same. means of solving the problem

[0013] In order to solve the aforementioned problem,

[0014] In one embodiment of the present invention,

[0015] An electrode assembly comprising an anode, a cathode, and a separator disposed between the anode and the cathode;

[0016] A battery case into which the above electrode assembly is inserted; and

[0017] The above battery case is injected with a thermosetting liquid electrolyte comprising a polymer having reactive acrylic groups, and

[0018] The above battery case has a coating layer comprising a binder and an azo-based thermal initiator on at least one of its inner surfaces;

[0019] The above-mentioned polymer having reactive acrylic groups is cross-linked by an azo-based thermal initiator of a coating layer provided on the inside of a battery case to form a gel polymer on the outside of an electrode assembly, thereby providing a lithium secondary battery.

[0020] At this time, the coating layer may comprise 80 to 99 weight percent of a binder and 1 to 20 weight percent of a thermal initiator.

[0021] In addition, the above azo thermal initiator may include a compound represented by the following chemical formula 1:

[0022] [Chemical Formula 1]

[0023]

[0024] In the above chemical formula 1,

[0025] X is a nitrile group, ester group, amidine group, or imidazole group;

[0026] R1 and R2 are each alkyl groups having 1 to 6 carbon atoms, or they bond to each other to form a cycloalkyl group having 3 to 7 carbon atoms together with the carbon atom to which they are all bonded, and

[0027] The above alkyl group is unsubstituted or substituted with an alkoxy group having 1 to 4 carbon atoms or a hydroxyl group.

[0028] As one example, the compound represented by Chemical Formula 1 above may include compounds represented by [Structural Formula 1] to [Structural Formula 6]:

[0029] [Structural Formula 1]

[0030]

[0031] [Structural Formula 2]

[0032]

[0033] [Structural Formula 3]

[0034]

[0035] [Structural Formula 4]

[0036]

[0037] [Structural Formula 5]

[0038]

[0039] [Structural Formula 6]

[0040]

[0041] In the above structural formulas 5 and 6,

[0042] R3 is each hydrogen or a hydroxyalkylene group having 1 to 4 carbon atoms, and

[0043] R4 is each hydrogen or a carboxyalkylene group having 2 to 6 carbon atoms, and

[0044] Y is H2O, HCl, H2SO4, HNO3, H3PO4.

[0046] In addition, the binder of the coating layer is polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polymethylmethacrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, polyethylene-co-vinylacetate, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethylpullulan, It may include one or more selected from the group consisting of cyanoethylpolyvinyl alcohol, cyanoethylcellulose, cyanoethylsucrose, pullulan, and carboxylmethylcellulose.

[0047] In addition, the polymer included in the thermosetting liquid electrolyte and having reactive acrylic groups may include a compound represented by the following chemical formula 2:

[0048] [Chemical Formula 2]

[0049]

[0050] In the above chemical formula 2,

[0051] X1 and X2 are respectively , or And,

[0052] Y1 and Y2 are respectively , , , or is,

[0053] Z1 and Z2 are *-CH2CH2-* or *-CH(CH3)CH2-*, respectively, and

[0054] R1, R2, R3, and R4 are each an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 10 carbon atoms, and

[0055] a is an integer from 2 to 200, and

[0056] b is an integer from 1 to 30, and

[0057] c is an integer from 1 to 6, and

[0058] d is an integer from 1 to 200.

[0060] As one example, the compound represented by the above chemical formula 2 may include one or more of the following [Structural Formula 7] to [Structural Formula 9]:

[0061] [Structural Formula 7]

[0062]

[0063] [Structural Formula 8]

[0064]

[0065] [Structural Formula 9]

[0066]

[0067] In the above structural formulas 7 to 9,

[0068] l is an integer from 1 to 100, and

[0069] m is an integer from 1 to 20, and

[0070] n is an integer from 1 to 30.

[0072] In addition, the polymer having the reactive acrylic group may be included in an amount of 1 to 15 weight percent based on the total weight of the thermosetting liquid electrolyte.

[0074] Furthermore, in one embodiment of the present invention,

[0075] A step of assembling a secondary battery by injecting a thermosetting liquid electrolyte into a battery case containing an electrode assembly comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode; and

[0076] It includes a step of heat-treating the assembled secondary battery, and

[0077] The above battery case has a coating layer comprising a binder and an azo-based thermal initiator on at least one of its inner surfaces, and

[0078] The above thermosetting liquid electrolyte comprises a polymer having reactive acrylic groups, and

[0079] The present invention provides a method for manufacturing a lithium secondary battery in which a polymer having the above-mentioned reactive acrylic group undergoes a cross-linking reaction with an azo-based thermal initiator of a coating layer provided on the inner side of the battery case during heat treatment of the secondary battery to form a gel polymer on the outer side of the electrode assembly.

[0080] At this time, the heat treatment step may be performed at 25 to 70°C for 0.1 to 10 hours. Effects of the invention

[0082] The lithium secondary battery according to the present invention has the advantage of excellent safety by preventing leakage of the liquid electrolyte while achieving high ionic conductivity, as it can selectively include a gel polymer at a high density on the outer side of the electrode assembly, specifically in the space between the electrode assembly and the battery case, by introducing a coating layer containing an azo-based thermal initiator on the inner side of the battery case into which the electrode assembly is inserted and inducing a cross-linking reaction between them by including a polymer having reactive acrylic groups in the liquid electrolyte. Specific details for implementing the invention

[0084] The present invention is capable of various modifications and may have various embodiments, and specific embodiments are to be described in detail in the detailed description.

[0085] However, this is not intended to limit the invention to specific embodiments, and it should be understood that it includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the invention.

[0086] In the present invention, terms such as "comprising" or "having" are intended to specify the existence of the features, numbers, steps, actions, components, parts, or combinations thereof described in the specification, and should be understood as not excluding in advance the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof.

[0087] Furthermore, in the present invention, when a part such as a layer, film, region, or plate is described as being "on" another part, this includes not only cases where it is "immediately above" the other part, but also cases where there is another part in between. Conversely, when a part such as a layer, film, region, or plate is described as being "under" another part, this includes not only cases where it is "immediately below" the other part, but also cases where there is another part in between. Additionally, in the present application, being "placed on" may include cases where it is placed on the lower part as well as on the upper part.

[0088] The terms "combination" or "connection" as used in the present invention include not only cases where one member and another member are directly combined or directly connected, but also cases where one member is indirectly combined or indirectly connected to another member through a connecting member.

[0090] The present invention will be described in more detail below.

[0092] lithium secondary battery

[0093] In one embodiment of the present invention,

[0094] An electrode assembly comprising an anode, a cathode, and a separator disposed between the anode and the cathode;

[0095] A battery case into which the above electrode assembly is inserted; and

[0096] The above battery case is injected with a thermosetting liquid electrolyte comprising a polymer having reactive acrylic groups, and

[0097] The above battery case has a coating layer comprising a binder and an azo-based thermal initiator on at least one of its inner surfaces;

[0098] The above-mentioned polymer having reactive acrylic groups is cross-linked by an azo-based thermal initiator of a coating layer provided on the inside of a battery case to form a gel polymer on the outside of an electrode assembly, thereby providing a lithium secondary battery.

[0100] A lithium secondary battery according to the present invention comprises an electrode assembly and a thermosetting liquid electrolyte, and includes a battery case in which they are housed and injected. At this time, the battery case has a coating layer containing a thermal initiator on at least one of its inner surfaces, and the thermosetting liquid electrolyte contains a polymer having reactive acrylic groups, wherein the thermal initiator of the coating layer and the polymer of the thermosetting liquid electrolyte undergo a cross-linking reaction to form a structure in which a gel polymer is selectively formed at a high density on the outer surface of the electrode assembly, specifically between the battery case and the electrode assembly.

[0101] The present invention has the advantage of effectively preventing leakage of the liquid electrolyte while achieving high ionic conductivity by forming a gel polymer at a high density between the battery case and the electrode assembly.

[0102] Here, the shape or structure of the battery case is not limited as long as it is commonly applied in the industry and can form a coating layer on the innermost side facing the electrode assembly.

[0103] As an example, the battery case may have a structure in which a metal layer, a polyolefin layer, and a coating layer are laminated from the outside to the inside.

[0104] In addition to the function of preventing the ingress or leakage of foreign substances such as gas and moisture, the metal layer can perform the function of improving the strength of the battery case, and may be, for example, a layer of aluminum.

[0105] In addition, the polyolefin layer may have low hygroscopicity and low electrolyte resistance so as not to be altered upon contact with the electrolyte, thereby having the function of inhibiting the intrusion of the electrolyte, and may be one or more selected from the group consisting of polypropylene (PP) and polyethylene (PE), and in some cases may include cross-linked polyethylene, cross-linked polypropylene, or a mixture thereof.

[0106] In addition, the coating layer includes an unreacted thermal initiator that does not react with the components constituting the coating layer, and can induce a gel reaction from the coating layer when in contact with a polymer having reactive acrylic groups contained in the liquid electrolyte. The gel polymers of the electrolyte generated through this process create a high density of gel polymers in the space between the battery case and the electrode assembly as described above, thereby preventing the liquid electrolyte impregnated in the electrode assembly from leaking out of the battery case, and thus further improving the safety of the secondary battery.

[0107] At this time, the thermal initiator may be applied considering its reactivity with a polymer having reactive acrylic groups contained in the liquid electrolyte, and preferably, an azo thermal initiator may be applied. The azo thermal initiator may include a compound represented by the following chemical formula 1:

[0108] [Chemical Formula 1]

[0109]

[0110] In the above chemical formula 1,

[0111] X is a nitrile group, ester group, amidine group, or imidazole group;

[0112] R1 and R2 are each alkyl groups having 1 to 6 carbon atoms, or they bond to each other to form a cycloalkyl group having 3 to 7 carbon atoms together with the carbon atom to which they are all bonded, and

[0113] The above alkyl group is unsubstituted or substituted with an alkoxy group having 1 to 4 carbon atoms or a hydroxyl group.

[0115] As one example, the compound represented by Chemical Formula 1 above may include compounds represented by [Structural Formula 1] to [Structural Formula 6]:

[0116] [Structural Formula 1]

[0117]

[0118] [Structural Formula 2]

[0119]

[0120] [Structural Formula 3]

[0121]

[0122] [Structural Formula 4]

[0123]

[0124] [Structural Formula 5]

[0125]

[0126] [Structural Formula 6]

[0127]

[0128] In the above structural formulas 5 and 6,

[0129] R3 is each hydrogen or a hydroxyalkylene group having 1 to 4 carbon atoms, and

[0130] R4 is each hydrogen or a carboxyalkylene group having 2 to 6 carbon atoms, and

[0131] Y is H2O, HCl, H2SO4, HNO3, or H3PO4.

[0133] The compound represented by Chemical Formula 1 above can easily induce a reaction of acrylic groups in a temperature range of 25°C to 75°C, specifically 25°C to 60°C, 25°C to 50°C, 25°C to 45°C, or 25°C to 35°C, without causing side reactions with components included in the coating layer, thus having the advantage of preventing side reactions that may occur inside the secondary battery before the initial charging / discharging or activation process of the battery.

[0134] In addition, the thermal initiator may be included in the coating layer in a specific amount. As previously mentioned, the thermal initiator does not react with the components included in the coating layer, but since it must induce gelation in the polymer having reactive acrylic groups of the liquid electrolyte injected after assembly of the secondary battery, it may be included in an amount of 1 to 20 wt%, more specifically 1 to 15 wt%, 1 to 10 wt%, 3 to 10 wt%, or 5 to 10 wt% based on the total weight of the coating layer.

[0135] The present invention prevents leakage of the liquid electrolyte caused by a significantly low content of the thermal initiator contained in the coating layer, which prevents the gel polymer from being sufficiently formed on the inner surface of the battery case due to a significantly low content, while also preventing side reactions with other active materials or a decrease in the cross-linking efficiency of the polymer before the cross-linking reaction of the polymer having reactive acrylic groups contained in the liquid electrolyte is induced due to an excessive amount of thermal initiator.

[0136] In addition, the thermal initiator may have a certain ratio with the binder contained in the coating layer. As one example, the coating layer may be composed of a binder and a thermal initiator, comprising 80 to 99 weight% and 1 to 20 weight%, respectively. As another example, the coating layer may be composed of inorganic particles, a binder, and a thermal initiator, comprising 89 to 95 weight% and 5 to 11 weight%, respectively.

[0137] Meanwhile, the binder included in the coating layer may be applied without particular limitation as long as it does not swell due to the liquid electrolyte, significantly increase in volume, or cause side reactions that reduce the performance of the battery; specifically, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polymethylmethacrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, polyethylene-co-vinylacetate, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, It may include one or more selected from the group consisting of cellulose acetate propionate, cyanoethylpullulan, cyanoethylpolyvinylalcohol, cyanoethylcellulose, cyanoethylsucrose, pullulan, and carboxylmethylcellulose.

[0138] Furthermore, the total thickness of the coating layer can be appropriately controlled within a range of 1 μm to 30 μm. The total thickness of the coating layer may refer to the average value of the thickness measured at any three points. If the thickness of the coating layer is less than 1 μm, the amount of thermal initiator included in the coating layer is insufficient, and a gel polymer may not be sufficiently formed on the inner surface of the battery case. On the other hand, if the coating layer is formed to be excessively thicker than the above thickness, the ion conductivity of the battery may be reduced, and the charge / discharge performance of the battery may be degraded.

[0139] In addition, the coating layer may further include inorganic particles along with a binder and a thermal initiator to achieve rigidity and flame retardancy of the battery case. The inorganic particles included in the coating layer are not particularly limited, as long as they are electrochemically stable.

[0140] As an example, the inorganic particles may include one or more of Al2O3, SiO2, TiO2, CaO, SrTiO3, BaTiO2, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al(OH)3, Mg(OH)2, and AlOOH.

[0141] In addition, the average diameter (D50) of the inorganic particles may range from 10 nm to 5 µm. If the average diameter (D50) of the particles is less than 10 nm, the surface area of ​​the inorganic particles is excessively high, which may reduce the dispersibility of the inorganic particles in the slurry when preparing a slurry for forming a coating layer. Meanwhile, as the mechanical properties of the separation membrane may deteriorate as the particle size of the inorganic particles increases, it is preferable not to exceed 5 µm.

[0142] In addition, the above-mentioned inorganic particles may be included in an amount of 1 to 30 weight% with respect to the total weight of the coating layer, and specifically, may be included in an amount of 1 to 20 weight%, 1 to 10 weight%, 5 to 20 weight%, or 10 to 30 weight%.

[0144] Meanwhile, the thermosetting liquid electrolyte comprises a polymer having reactive acrylic groups that react with a thermal initiator contained in the coating layer of the battery case. In this case, the polymer is a compound represented by the following chemical formula 2, and can form a network bonded in a three-dimensional structure by containing two or more reactive acrylic groups:

[0145] [Chemical Formula 2]

[0146]

[0147] In the above chemical formula 2,

[0148] X1 and X2 are respectively , or And,

[0149] Y1 and Y2 are respectively , , , or is,

[0150] Z1 and Z2 are *-CH2CH2-* or *-CH(CH3)CH2-*, respectively, and

[0151] R1, R2, R3, and R4 are each an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 10 carbon atoms, and

[0152] a is an integer from 2 to 200, and

[0153] b is an integer from 1 to 30, and

[0154] c is an integer from 1 to 6, and

[0155] d is an integer from 1 to 200.

[0157] As one example, the compound represented by the above chemical formula 2 may include one or more of the following [Structural Formula 7] to [Structural Formula 9]:

[0158] [Structural Formula 7]

[0159]

[0160] [Structural Formula 8]

[0161]

[0162] [Structural Formula 9]

[0163]

[0164] In the above structural formulas 7 to 9,

[0165] l is an integer from 1 to 100, and

[0166] m is an integer from 1 to 20, and

[0167] n is an integer from 1 to 30.

[0169] The compound represented by Chemical Formula 2 above contains two or more acrylic groups at the ends, so it can form a three-dimensional network upon gelation, thereby improving the mechanical strength of the secondary battery itself. In addition, the compound represented by Chemical Formula 2 above contains urethane groups having cyclic hydrocarbon groups, which can improve the ion transport characteristics of the gel polymer.

[0170] The polymer having the reactive acrylic group may be included in the liquid electrolyte in a certain proportion to uniformly form a gel polymer at the interface between the anode and / or cathode and the separator. Specifically, the polymer may be included in an amount of 1 to 15 weight% with respect to the total weight of the liquid electrolyte, and more specifically, in an amount of 1 to 12 weight%; 3 to 10 weight%; or 5 to 13 weight% with respect to the total weight of the liquid electrolyte. By controlling the content of the polymer having the reactive acrylic group contained in the liquid electrolyte to the above range, the present invention can not only sufficiently generate a gel polymer in the space between the battery case and the electrode assembly, but also prevent the ion conductivity of the battery from decreasing due to an excess amount of gel polymer.

[0171] In addition, the liquid electrolyte may further include a lithium salt and an electrolyte solvent together with a polymer having reactive acrylic groups.

[0172] The above lithium salts may be applied without particular limitation as long as they are used in the industry for non-aqueous electrolytes. Specifically, the above lithium salts are LiCl, LiBr, LiI, LiClO4, LiBF4, and LiB 10 It may include one or more selected from the group consisting of Cl10, LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)2NLi and (FSO2)2NLi.

[0173] There are no specific restrictions on the concentration of these lithium salts, but the lower limit of the appropriate concentration range is 0.5 mol / L or higher, specifically 0.7 mol / L or higher, more specifically 0.9 mol / L or higher, and the upper limit is 2.5 mol / L or lower, specifically 2.0 mol / L or lower, more specifically 1.5 mol / L or lower. If the concentration of the lithium salt is lower than 0.5 mol / L, the ion conductivity decreases, which may lead to a decrease in the cycle characteristics and output characteristics of the non-aqueous electrolyte battery. In addition, if the concentration of the lithium salt exceeds 2.5 mol / L, the viscosity of the electrolyte for the non-aqueous electrolyte battery increases, which may also lead to a decrease in ion conductivity and a decrease in the cycle characteristics and output characteristics of the non-aqueous electrolyte battery.

[0174] In addition, when a large amount of lithium salt is dissolved in a non-aqueous organic solvent at once, the liquid temperature may rise due to the heat of dissolution of the lithium salt. If the temperature of the non-aqueous organic solvent rises significantly due to the heat of dissolution of the lithium salt in this way, in the case of a lithium salt containing fluorine, decomposition is accelerated and there is a risk of hydrogen fluoride (HF) being generated. Hydrogen fluoride (HF) is undesirable because it causes degradation of battery performance. Therefore, the temperature at which the lithium salt is dissolved in the non-aqueous organic solvent is not particularly limited, but can be controlled to -20 to 80°C, and specifically to 0 to 60°C.

[0175] In addition, the non-aqueous organic solvent used in the above electrolyte composition can be applied without particular limitation as long as it is used in the industry for non-aqueous electrolytes. Specifically, the above-mentioned non-aqueous organic solvents include, for example, N-methyl-2-pyrrolidinone, ethylene carbonate (EC), propylene carbonate (PC), propylene carbonate, butylene carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), gamma-butyrolactone, 1,2-dimethoxyethane (DME), tetrahydroxyfranc, 2-methyl tetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolone, formamide, dimethylformamide, dioxolone, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphate triester, trimethoxymethane, dioxolone derivative, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivative, tetrahydrofuran derivative, ether, propionic acid Aprotic organic solvents such as methyl (MP), ethyl propionate (EP), and propyl propionate (PP) can be used.

[0176] In addition, the non-aqueous organic solvent used in the present invention may be used as a single type, or two or more types may be mixed in any combination or ratio according to the application. Among these, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, diethyl carbonate, dimethyl carbonate, and ethylmethyl carbonate are particularly preferred in terms of electrochemical stability against oxidation and reduction and chemical stability against reaction with heat or solutes.

[0177] Furthermore, the liquid electrolyte may not contain an initiator. The liquid electrolyte may not contain a thermal initiator and / or a photoinitiator to prevent the polymer having reactive acrylic groups from performing a crosslinking reaction in a region other than the interface between the electrode and the separator.

[0179] Meanwhile, the electrode assembly has a structure comprising an anode, a cathode, and a separator disposed between the anode and the cathode as described above.

[0180] At this time, the anode comprises an anode composite layer manufactured by applying, drying, and pressing an anode active material onto an anode current collector, and may optionally further include a conductive material, a binder, other additives, etc., as needed.

[0181] Here, the positive active material is a material capable of causing an electrochemical reaction on a positive current collector and may include one or more of the lithium metal oxides represented by Formula 3 or Formula 4 that are capable of reversibly intercalating and deintercalating lithium ions.

[0182] [Chemical Formula 3]

[0183] Li x [Ni y Co z Mn w M 1 v ]O2

[0184] [Chemical Formula 4]

[0185] Li a Fe 1-b M 2 b PO4

[0186] In the above chemical formulas 3 and 4,

[0187] M 1 It is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and

[0188] x, y, z, w, and v are respectively 1.0≤x≤1.30, 0≤y<1, 0≤z≤1, 0≤w≤1, and 0≤v≤0.1, where y+z+w+v=1, and

[0189] M 2is one or more selected from Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y, and

[0190] a and b are 0.5≤a≤1.5 and 0≤b≤0.5, respectively.

[0191] When the lithium metal oxide represented by the above chemical formula 3 or chemical formula 4 is used as a positive electrode active material, it has the advantage of being able to stably supply high capacity and / or high voltage electricity.

[0192] In this case, the lithium metal oxide represented by the above chemical formula 3 is lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2, LiMn2O4, etc.), lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O2, LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 It may include O2, etc.

[0193] In addition, the lithium metal oxide represented by the above chemical formula 4 is LiFePO4, LiFe 0.7 Mn 0.3 It may include PO4, etc., and may be used alone or in combination.

[0194] In addition, the anode may be used as an anode current collector that has high conductivity without causing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, etc. may be used, and in the case of aluminum or stainless steel, surface-treated materials such as carbon, nickel, titanium, silver, etc. may be used. Furthermore, the average thickness of the current collector may be appropriately applied in the range of 5 to 500 μm, taking into consideration the conductivity and total thickness of the anode being manufactured.

[0195] In addition, the above-mentioned cathode, like the anode, comprises a cathode composite layer manufactured by applying, drying, and pressing a cathode active material onto a cathode current collector, and may optionally further include a conductive material, a binder, other electrolyte additives, etc., as needed.

[0196] The above-mentioned cathode active material may include a carbon material. Specifically, the carbon material refers to a material having carbon atoms as its main component, and such carbon material may include one or more selected from the group consisting of natural graphite, artificial graphite, expanded graphite, non-graphitized carbon, carbon black, acetylene black, and Ketjen black.

[0197] In addition, the above-mentioned negative electrode active material may further include a silicon material along with a carbon material. The silicon material refers to a material having silicon atoms as its main component, and such silicon material may include silicon (Si), silicon carbide (SiC), silicon monoxide (SiO), or silicon dioxide (SiO2) alone or in combination. When silicon monoxide (SiO) and silicon dioxide (SiO2) are uniformly mixed or composited and included in the negative electrode composite layer as the silicon (Si)-containing material, they may be represented as silicon oxide (SiOq, provided that 0.8≤q≤2.5).

[0198] In addition, the silicon material may be included in an amount of 1 to 20 weight% with respect to the total weight of the negative electrode active material, and specifically, may be included in an amount of 3 to 10 weight%; 8 to 15 weight%; 13 to 18 weight%; or 2 to 8 weight%. The present invention can maximize the energy density of the battery by controlling the content of the silicon material to the above-mentioned content range.

[0199] In addition, the above-mentioned negative electrode current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and for example, copper, stainless steel, nickel, titanium, calcined carbon, etc. may be used, and in the case of copper or stainless steel, surface-treated carbon, nickel, titanium, silver, etc. may be used. Furthermore, the average thickness of the above-mentioned negative electrode current collector can be appropriately applied in the range of 1 to 500 μm, taking into consideration the conductivity and total thickness of the negative electrode being manufactured.

[0200] In addition, the separator interposed between the anode and the cathode is an insulating thin film having high ion permeability and mechanical strength, and is not particularly limited as long as it is commonly used in the industry; specifically, it may be used as one comprising one or more polymers selected from chemically resistant and hydrophobic polypropylene; polyethylene; and polyethylene-propylene copolymer. The separator may have the form of a porous polymer substrate, such as a sheet or nonwoven fabric, containing the polymer described above, and in some cases, it may have the form of a composite separator in which organic or inorganic particles are coated on the porous polymer substrate by an organic binder. Furthermore, the separator may have an average pore diameter of 0.01 to 10 μm and an average thickness of 5 to 300 μm.

[0202] Method for manufacturing a lithium secondary battery

[0203] In addition, in one embodiment of the present invention,

[0204] A step of assembling a secondary battery by injecting a thermosetting electrolyte into a battery case containing an electrode assembly comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode; and

[0205] It includes a step of heat-treating the assembled secondary battery, and

[0206] The above battery case has a coating layer comprising a binder and an azo-based thermal initiator on at least one of its inner surfaces, and

[0207] The above thermosetting electrolyte comprises a polymer having reactive acrylic groups, and

[0208] The present invention provides a method for manufacturing a lithium secondary battery in which a polymer having the above-mentioned reactive acrylic group undergoes a cross-linking reaction with an azo-based thermal initiator of a coating layer provided on the inner side of the battery case during heat treatment of the secondary battery to form a gel polymer on the outer side of the electrode assembly.

[0210] The method for manufacturing a lithium secondary battery according to the present invention can be performed by assembling a secondary battery by injecting a thermosetting liquid electrolyte into a battery case containing an electrode assembly including a positive electrode, a negative electrode, and a separator, and by heat-treating the assembled secondary battery.

[0211] At this time, the battery case includes a coating layer comprising a binder and an azo-based thermal initiator on at least one surface, and when heat-treating the assembled secondary battery, a cross-linking reaction of a polymer having reactive acrylic groups included in a liquid electrolyte is induced in the space between the inner surface of the battery case and the surface of the electrode assembly to form a gel polymer.

[0212] In addition, to induce a cross-linking reaction between a thermal initiator included in the coating layer of the battery case and a polymer having reactive acrylic groups included in the liquid electrolyte, and to suppress side reactions of each component included in the secondary battery before initial charging and discharging, the heat treatment step may be controlled in terms of the heat treatment temperature and execution time within a specific range.

[0213] Specifically, the heat treatment step can be performed at a temperature of 25°C to 75°C, and more specifically, at a temperature of 25°C to 60°C, 25°C to 50°C, 25°C to 45°C, or 25°C to 35°C.

[0214] In addition, the heat treatment step may be performed for 0.1 to 10 hours, and specifically, for 1 to 10 hours; 3 to 8 hours; or 5 to 10 hours.

[0215] The method for manufacturing a lithium secondary battery according to the present invention can generate a gel polymer at a high density in the space between the inner surface of the battery case and the outer surface of the electrode assembly without inducing side reactions inside the secondary battery by controlling the conditions during heat treatment as described above.

[0217] The present invention will be explained in more detail below through examples and experimental examples.

[0218] However, the following examples and experimental examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples.

[0221] Example.

[0222] a) Preparation of a battery case for a lithium secondary battery

[0223] First, an aluminum foil with a thickness of 40 μm (product of Dongil Aluminum Co.) was immersed in a 5% sulfuric acid solution to degrease it with acid, and then immersed again in a 5% sodium hydroxide solution to activate the surface. Subsequently, a polyurethane adhesive resin with a thickness of 4 μm (product of Hichem Co.) was applied, and then a polypropylene film (average thickness: 25 μm) was laminated onto one side of the aluminum foil coated with the polyurethane adhesive resin to prepare a laminate.

[0224] Separately, a slurry for forming a coating layer was prepared by weighing and mixing N-methylpyrrolidone, a solvent, inorganic particles Al2O3 (D50: 500 nm), polyvinylidene fluoride (PVdF), a binder, and the compounds shown in Table 1 below as thermal initiators as shown in Table 1.

[0225] A prepared slurry was applied onto a polyethylene film of a pre-prepared laminate and dried at a temperature of 60°C to form a coating layer with a thickness of 10 μm, and the laminate was sealed in a pouch shape so that the formed coating layer was positioned on the inside to manufacture a battery case (total thickness: 35 μm).

[0226] Inorganic particles bookbinder Thermal initiator type Content Example 1 20 79.9 [Structural Formula 3] 0.1 Example 2 20 72 8 Example 3 20 55 25 Example 4 20 72 [Structural Formula 1] 8 Example 5 20 72 [Structural Formula 5] Y=2HCl 8

[0228] b) Manufacturing of lithium secondary batteries

[0229] LiNi with a particle size of 5㎛ as a cathode active material 0.8 Co 0.1 Mn 0.1 O2 was prepared, and a slurry was formed by mixing it with N-methylpyrrolidone (NMP) in a weight ratio of 94:3:3 as a carbon-based conductive agent and binder, and then casting it onto an aluminum foil, drying it in a vacuum oven at 120°C, and rolling it to produce an anode.

[0230] Separately, a negative electrode active material was prepared by mixing natural graphite and artificial graphite in a weight ratio of 1:1, and 97 parts by weight of the negative electrode active material and 3 parts by weight of styrene-butadiene rubber (SBR) were mixed with water to form a slurry, cast onto a copper foil, dried in a vacuum oven at 130°C, and then rolled to manufacture a negative electrode.

[0231] A pouch-type lithium secondary battery was assembled by interposing a separator made of 18 μm thick polypropylene between the anode and cathode obtained above, inserting it into a previously manufactured case, and then injecting a liquid electrolyte (5 ml).

[0232] At this time, the liquid electrolyte was prepared by dissolving LiPF6, a lithium salt, at a concentration of 1 M in a solvent mixed with ethylene carbonate (EC), ethylmethyl carbonate (EMC), ethylpropionate (EP), and propylpropionate (PP) in a volume ratio of 1:1:1:1, and by weighing and dissolving a compound represented by structural formula 7 as an electrolyte additive at a concentration of 10% by weight relative to the total weight of the liquid electrolyte.

[0233] A lithium secondary battery was manufactured by mounting the assembled lithium secondary battery in an oven and heat-treating it in a 40°C oven for 10 hours.

[0234] [Structural Formula 7]

[0235]

[0236] Types of battery cases Example 6 Battery case of Example 1 Example 7 Battery case of Example 2 Example 8 Battery case of Example 3 Example 9 Battery case of Example 4 Example 10 Battery case of Example 5

[0239] Comparative Example 1.

[0240] A lithium secondary battery was manufactured by performing the same method as in Example 2, except that ① a case in which a coating layer is not formed and ② a liquid electrolyte containing 8% by weight of the thermal initiator represented by [Structural Formula 3] with respect to the total weight were used.

[0242] Comparative Example 2.

[0243] A lithium secondary battery was manufactured by performing the same method as in Example 2, except that benzoyl peroxide was used as the thermal initiator.

[0245] Experimental Example 1.

[0246] In order to confirm the formation location of the gel polymer and the resulting stability improvement effect in the lithium secondary battery according to the present invention, the following experiment was performed.

[0247] First, the theoretical weight of the gel polymer, which is the product obtained during the cross-linking reaction of the polymer represented by [Structural Formula 7] contained in the liquid electrolyte, was calculated.

[0248] Then, the lithium secondary batteries prepared in Example 2, Comparative Examples 1 and 2 were disassembled, and the electrolyte contained in the battery case was filtered through a 500 mesh (pore size 100 μm) mesh to obtain the insoluble material, and the dry mass of the insoluble material was measured to calculate the content of the gel polymer remaining in the liquid electrolyte.

[0249] Afterward, the electrode assembly was removed from the battery case, and the inner surface of the battery case and the outer surface of the electrode assembly were washed with ethyl acetate while the electrolyte was filtered through a 500 mesh (pore size 100㎛) mesh to obtain the insoluble material. The dry mass of the insoluble material was measured to calculate the content of the gel polymer present at the interface between the electrode and the separator.

[0250] Based on the theoretical weight of the gel polymer calculated earlier, ⓐ the content ratio of the gel polymer remaining in the liquid electrolyte and ⓑ the content ratio of the gel polymer existing in the space between the inner surface of the battery case and the outer surface of the electrode assembly were calculated.

[0251] As a result, it was confirmed that the lithium secondary battery prepared in Example 2 had a gel polymer content of less than 5 wt% in the liquid electrolyte and a gel polymer content of 90 wt% or more in the space between the inner surface of the battery case and the outer surface of the electrode assembly.

[0252] In contrast, the lithium secondary battery manufactured in Comparative Example 1 was found to have a gel polymer content of 80 wt% or more in the liquid electrolyte and a gel polymer content of less than 10 wt% in the space between the inner surface of the battery case and the outer surface of the electrode assembly.

[0253] In addition, the lithium secondary battery prepared in Comparative Example 2 was found to have a content of gel polymer present in the liquid electrolyte and a content of gel polymer present in the space between the inner surface of the battery case and the outer surface of the electrode assembly of 20-30 wt% and 20-40 wt%, respectively, indicating that the cross-linking reaction of the polymer represented by [Structural Formula 7] was not sufficiently carried out.

[0254] From these results, it can be seen that in the lithium secondary battery according to the present invention, a gel polymer is selectively formed at a high density on the inner surface of the battery case, thereby making it difficult for the liquid electrolyte to leak out.

[0256] Experimental Example 2.

[0257] To evaluate the electrical performance of the lithium secondary battery according to the present invention, the following experiment was performed.

[0258] Specifically, the charge / discharge capacity was measured for the lithium secondary batteries prepared in the examples and comparative examples, respectively. Specifically, the activation charge / discharge of the lithium secondary battery was performed twice at 0.2C / 0.5C, and then a standard charge / discharge current density was set to 0.5C / 0.2C, and a charge / discharge experiment was performed once each with a charge termination voltage of 4.8V (Li / graphite) and a discharge termination voltage of 3.0V (Li / graphite). The capacity of the activated secondary battery was measured by performing charge / discharge under conditions of 25℃ and 70mAh / 3mAh, and the results are shown in Table 3 below.

[0259] Charge / Discharge Capacity [mAh] Example 6 894 Example 7 889 Example 8 875 Example 9 881 Example 10 893 Comparative Example 1 689 Comparative Example 2 883

[0261] As shown in Table 3 above, it can be seen that the lithium secondary battery according to the present invention has excellent ion conductivity and high electrical performance. Specifically, it was confirmed that the lithium secondary batteries manufactured in the examples exhibited improved ion conductivity and a charge / discharge capacity of 875 mAh or more.

[0263] From these results, it can be seen that the lithium secondary battery according to the present invention has excellent safety by preventing leakage of the liquid electrolyte while achieving high ionic conductivity, by introducing a coating layer containing an azo-based thermal initiator on the inner surface of a battery case into which an electrode assembly is inserted, and by including a polymer having reactive acrylic groups in the liquid electrolyte to induce a cross-linking reaction between them, the gel polymer is selectively included at a high density on the outer surface of the electrode assembly, specifically in the space between the electrode assembly and the battery case.

[0265] Although the present invention has been described above with reference to preferred embodiments, those skilled in the art or those with ordinary knowledge in the art will understand that various modifications and changes can be made to the present invention without departing from the spirit and technical scope of the invention as described in the claims set forth below.

[0266] Therefore, the technical scope of the present invention should not be limited to the contents described in the detailed description of the specification, but should be determined by the claims.

Claims

Claim 1 A lithium secondary battery comprising: an electrode assembly including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode; a battery case into which the electrode assembly is inserted; and a thermosetting liquid electrolyte injected into the battery case and comprising a polymer having reactive acrylic groups, wherein the battery case has a coating layer comprising a binder and an azo-based thermal initiator on at least one of its inner surfaces; wherein the polymer having reactive acrylic groups undergoes a cross-linking reaction by the azo-based thermal initiator of the coating layer provided on the inner side of the battery case to form a gel polymer on the outer side of the electrode assembly, and wherein the polymer having reactive acrylic groups comprises a compound represented by the following chemical formula 2: [Chemical Formula 2] In the above chemical formula 2, X1 and X2 are respectively , or And, Y1 and Y2 are respectively , , , or Z1 and Z2 are each *-CH2CH2-* or *-CH(CH3)CH2-*, R1, R2, R3 and R4 are each an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 10 carbon atoms, a is an integer from 2 to 200, b is an integer from 1 to 30, c is an integer from 1 to 6, and d is an integer from 1 to 200. Claim 2 A lithium secondary battery according to claim 1, wherein the coating layer comprises 80 to 99 weight% of a binder and 1 to 20 weight% of a thermal initiator. Claim 3 In claim 1, the azo thermal initiator comprises a compound represented by the following chemical formula 1, in a lithium secondary battery: [Chemical Formula 1] In the above chemical formula 1, X is a nitrile group, an ester group, an amidin group, or an imidazole group; R1 and R2 are each alkyl groups having 1 to 6 carbon atoms, or they are bonded to each other to form a cycloalkyl group having 3 to 7 carbon atoms together with the carbon atoms to which they are all bonded, and the alkyl group is unsubstituted or substituted with an alkoxy group having 1 to 4 carbon atoms or a hydroxyl group. Claim 4 In paragraph 3, the compound represented by Chemical Formula 1 is a lithium secondary battery comprising compounds represented by [Structural Formula 1] to [Structural Formula 6]: [Structural Formula 1] [Structural Formula 2] [Structural Formula 3] [Structural Formula 4] [Structural Formula 5] [Structural Formula 6] In the above structural formulas 5 and 6, R3 is each hydrogen or a hydroxyalkylene group having 1 to 4 carbon atoms, R4 is each hydrogen or a carboxyalkylene group having 2 to 6 carbon atoms, and Y is H2O, HCl, H2SO4, HNO3, or H3PO4. Claim 5 In claim 1, the binder of the coating layer is polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polymethylmethacrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, polyethylene-co-vinylacetate, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethylpullulan, A lithium secondary battery comprising one or more selected from the group consisting of cyanoethylpolyvinyl alcohol, cyanoethylcellulose, cyanoethylsucrose, pullulan, and carboxylmethylcellulose. Claim 6 delete Claim 7 In claim 1, the compound represented by Chemical Formula 2 comprises one or more of the following [Structural Formula 7] to [Structural Formula 9], forming a lithium secondary battery: [Structural Formula 7] [Structural Formula 8] [Structural Formula 9] In the above structural formulas 7 to 9, l is an integer from 1 to 100, m is an integer from 1 to 20, and n is an integer from 1 to 30. Claim 8 A lithium secondary battery according to claim 1, wherein the polymer having reactive acrylic groups is included in an amount of 1 to 15 weight percent based on the total weight of the thermosetting liquid electrolyte. Claim 9 A method for manufacturing a lithium secondary battery according to claim 1, comprising: a step of assembling a secondary battery by injecting a thermosetting liquid electrolyte into a battery case containing an electrode assembly comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode; and a step of heat-treating the assembled secondary battery, wherein the battery case has a coating layer comprising a binder and an azo-based thermal initiator on at least one of its inner surfaces, and the thermosetting liquid electrolyte comprises a polymer having reactive acrylic groups, and the polymer having reactive acrylic groups undergoes a cross-linking reaction by the azo-based thermal initiator of the coating layer provided on the inner side of the battery case during heat treatment of the secondary battery to form a gel polymer on the outer side of the electrode assembly. Claim 10 A method for manufacturing a lithium secondary battery according to claim 9, wherein the heat treatment step is performed at 25 to 70°C. Claim 11 A method for manufacturing a lithium secondary battery according to claim 9, wherein the heat treatment step is performed for 0.1 to 10 hours.

Citation Information

Patent Citations

  • Secondary battery and manufacturing method of the same

    KR1020080101702A

  • Pouch case for lithium secondary battery and lithium secondary battery comprising the same

    KR1020190106780A

  • Battery

    JP2006278272A

  • Method of preparing gel polymer electrolyte secondary battery and Gel polymer electrolyte secondary battery

    KR1020100016919A